Adaptability of Helietta parvifolia to Extreme Climatic Conditions of North-eastern Mexico - Foroughbakhch, Rahim; Piñero, Jorge L. Hernández; Vázquez, Marco A. Alvarado; Parra, Artemio Carrillo (International Journal of Bio-resource and Stress Management, 2010)
In rural zones of Mexico, the demand for timber and forest product continues to increase. Efforts are being made to meet the demand for timber by raising compensatory man-made plantations. Presently, attention is given to growing indigenous premium hardwood species. One of the promising indigenous species among various fuelwood species is Helietta parvifolia which grows naturally in the dry and sub-tropical zones of north-eastern Mexico. It is a premium quality hardwood species and the wood is of high density which is used for construction and furniture. This paper describes its structure, growth characteristics and the economic yield in north-eastern Mexico. H. parvifolia was sampled in seven study sites of native vegetation. The average population density was 1210 plants ha-1. Three strata were found: a low stratum along with sub-chaparral less than 3 m in height; a chaparral stratum with 3-5 m height (3-6 cm dbh), and a third stratum higher than 6 m in height and 7-12 cm in dbh (diameter at breast height). The principal component analysis indicated 75% of the biomass as wood product and 25% as foliage and debris. The economic yield was 1455 fence posts ha-1 with a dbh superior than 7 cm, corresponding to an income of USD 1892 ha-1.